What is important in the surroundings in order to extend the healthy life period? A regional study of 19 older women in a northern part of Norway - Minde, Gunn-Tove; Sæterstrand, Torill Margaret (International Journal of Circumpolar Health, 2015)
Introduction: Participating in a community with other retired individuals to increase life quality can be possible for the older persons. Cultural and ethnical background is important for their social identity. Objective: To identify what the informants think is important in their surroundings in order to extend their healthy life period. Study design: A structured questionnaire developed by the OCIN network. Methods: Nineteen elderly women aged 75 years or more were interviewed. The regional survey is a pilot study in Norway. The data were collected during 2 periods, in 2009 and 2010. The data is analyzed using a result scheme prepared by the network OCIN. Results: Our findings show that this is a group of elderly women that are concerned with promoting their own health. The participants wish to take care of themselves so they do not become a burden for society and the local authorities. Conclusions: The findings of this study suggest that participation in the local context is important for promoting health and well-being among elderly in all ethnicities. For the Sami elderly, this is particularly important because meeting equal minded people helps them maintain their Sami identity. In the Sami culture and among the Sami elderly, it is important to be “strong” and “healthy”. Due to these norms, the elderly Sami women try to live with their illnesses and are less eager to go to the doctor when they are serious ill. Keywords: elderly women, Sami elderly women, activity, health, participation